Pelatihan Dan Pendampingan Akuntabilitas Dalam Pengelolaan Dana Seni Dan Kirab Budaya Pada Desa Cupak Jombang - Irda Agustin Kustiwi; Binti Yuliatin; Dhea Rizky Istiqomah; Nur Wahyu Satriwibowo; Adelia Febriana; Gusti Chania Raafi Iradati (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
Accountability in village governance is crucial to ensure responsible government oversight of village financial management and prevent misappropriation. Cupak Village, renowned as a religious tourism destination in Gunung Pucangan, possesses potential in the craft of weaving mats using pandan leaves. However, the village community lacks the capacity to fully utilize this potential as an additional source of income. To address various issues faced by the community, particularly in establishing accountability in event fund management for a cultural parade called "Kirab Budaya," a community engagement activity called the "Matching Fund Kedaireka 2022" was conducted in Cupak Village, Ngusikan District, Jombang Regency. The implementation aimed to generate significant outcomes in the planning of the cultural parade event, enhance the sustainability of community welfare, and boost the economic potential of Cupak Village. The arts and cultural program employed various approaches, including socialization, training, and mentoring. The training program was designed to provide the community with understanding and skills related to financial matters and accountability in fund management.